2014
DOI: 10.1089/neu.2013.3252
|View full text |Cite
|
Sign up to set email alerts
|

CCR2 Deficiency Impairs Macrophage Infiltration and Improves Cognitive Function after Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) provokes inflammatory responses, including a dramatic rise in brain macrophages in the area of injury. The pathway(s) responsible for macrophage infiltration of the traumatically injured brain and the effects of macrophages on functional outcomes are not well understood. C-C-chemokine receptor 2 (CCR2) is known for directing monocytes to inflamed tissues. To assess the role of macrophages and CCR2 in TBI, we determined outcomes in CCR2-deficient (Ccr2 -/ -) mice in a controlled cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(150 citation statements)
references
References 80 publications
9
138
1
Order By: Relevance
“…58 Mild or severe traumatic brain injury induces hyperactivity in male and female mice Significant hyperactive exploration in the OF is a frequently reported effect of CCI delivered over parietal cortex in mice. 33,[59][60][61][62][63] In the current experiment, hyperactivity in injured mice ( Fig. 2A,B) was the result of more-continuous exploration in mice with TBI (fewer starts and stops; Fig.…”
Section: Females Are More Active During the First Exposure To Open Fieldmentioning
confidence: 53%
See 1 more Smart Citation
“…58 Mild or severe traumatic brain injury induces hyperactivity in male and female mice Significant hyperactive exploration in the OF is a frequently reported effect of CCI delivered over parietal cortex in mice. 33,[59][60][61][62][63] In the current experiment, hyperactivity in injured mice ( Fig. 2A,B) was the result of more-continuous exploration in mice with TBI (fewer starts and stops; Fig.…”
Section: Females Are More Active During the First Exposure To Open Fieldmentioning
confidence: 53%
“…3C,D), corroborating previous findings in C57BL/6 mice when tested in an OF after parietal CCI. 33,59,62 However, testing of anxiety in the classic elevated plus maze (EPM) post-TBI yields disparate results. Washington and colleagues 72 reported that cortically injured mice spent a greater amount of time in anxiogenic regions of the EPM on the 20th day postinjury and concluded that brain injury results in increased ''risk-taking'' behaviors in mice.…”
Section: Severe Traumatic Brain Injury Induces Anxiety Equally In Malmentioning
confidence: 99%
“…Previous work has been limited to acute injury responses immediately following injury where a robust inflammatory response characterized by immunecell infiltration into the brain (34,(43)(44)(45)(46)(47), cytokine production (39,40,(48)(49)(50), and reactive oxygen species release (51-53) lead to neuronal death. Thus, strategies to counteract acute injurymediated effects have aimed to dampen the inflammatory response (43,44,52,54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with wild-type mice, CCR2 knockout mice subjected to CCI have reduced lesion volumes, decreased pro-inflammatory gene expression, decreased macrophage infiltration in the injured cortex and improved cognitive function recovery after TBI. 32,33 Morganti and colleagues recently evaluated a CCR2 antagonist (CCX872) in CX3CR1GFP/+CCR2RFP/+ reporter mice using the 34 CCR2 antagonism also improved cognitive function recovery after TBI, as demonstrated by increased performance of CCX872-treated mice in a radial arm water maze test at 28 days post-injury. 34 They also showed that CCR2-positive infiltrating macrophages in the brain expressed both M1-and M2-like markers acutely after TBI, with sequential activation of M1-, followed by M2a-, and finally M2c-marker expression.…”
Section: Fig 7 (Continued)mentioning
confidence: 99%